Quantification of paramagnetic ions in human brain tissue: correlation to quantitative magnetic resonance imaging - Otsuka, Fábio Seiji (2023)
Quantitative Magnetic Resonance Imaging (qMRI) is emerging as a promising tool to quantify iron in vivo through R2* and Quantitative Susceptibility Mapping (QSM) techniques, however their relationship to iron and its molecular forms is still unknown. Therefore, this study aims to evaluate the relationship between R2* and QSM\'s contrast and different metals concentrations assessed by Inductive Coupled-Plasm Mass Spectrometry and Electron Paramagnetic Resonance (EPR). A total of 15 postmortem subjects were recruited with death by non-neurological factors. Postmortem images were processed for R2* and QSM maps, and nine relevant gray matter regions were manually segmented and assessed. Absolute metal concentration was quantified by means of ICP-MS and the paramagnetic ion content by EPR. This study corroborated that iron is the main source of contrast in the imaging techniques R2 and QSM, with a stronger relationship in the structures of the basal ganglia. However, the contrast seems to be locally dependent, and in this study four classes or groups of anatomical regions were identified. The first group consisted of regions that strongly correlated to both total iron and the paramagnetic ion attributed to the ferritin protein. The second group consisted of regions which showed only partial correlation and therefore, may not be totally related to iron and should be carefully evaluated when interpreting their contrast. Substantia Nigra is in the third class, which showed good correlation to total iron, however not to the ferritin protein, indicating a different main contrast mechanism for this structure. Lastly, the fourth group didn\'t correlate to iron and ferritin. This study indicates a heterogeneous participation of iron in the contrast of R2* and QSM across different gray matter regions, indicating that regions with low iron concentrations are influenced by other factor that were not investigated in this study. Furthermore, among the iron-rich structures that were correlated iron, there seems to be different molecular iron forms associated to their contrast. Specifically, the Substantia Nigra showed poor correlation to the ferritin signal, suggesting other contrast mechanism.